Respuesta :
First we get the value of y in terms of x
We have 2x + y + 9 = 0
We transpose 2x and 9 to the other side so we could get the value of y being:
y = - 2x - 9
Now that we have the value of y we can substitute it to the first equation
6x - 3y + 10 = 0
6x - 3 (-2x - 9) + 10 = 0
Simplifying the inside of the parentheses we would have
6x - (3)(-2x) - (3)(-9) + 10 =0
6x + 6x + 27 + 10 = 0
Combining similar terms we would get
12x + 37 = 0
We transpose 37 to the other side for easier simplification
12x = - 37
We divide both sides by 12 to get the value of x
12x/12 = - 37/12
Since 12/12 is equal to 1 our value of x would be
x = - 37/12
Or simply x = - 3.0833
Now that we know the value of x we can use it to obtain the value of y
y = - 2x - 9
y = - 2(-37/12) - 9
y = 37/6 - 9
y = - 17/6
Or in decimal y = - 2.8333
Final values of x and y would be
x = - 3.0833
y = - 2.8333
We have 2x + y + 9 = 0
We transpose 2x and 9 to the other side so we could get the value of y being:
y = - 2x - 9
Now that we have the value of y we can substitute it to the first equation
6x - 3y + 10 = 0
6x - 3 (-2x - 9) + 10 = 0
Simplifying the inside of the parentheses we would have
6x - (3)(-2x) - (3)(-9) + 10 =0
6x + 6x + 27 + 10 = 0
Combining similar terms we would get
12x + 37 = 0
We transpose 37 to the other side for easier simplification
12x = - 37
We divide both sides by 12 to get the value of x
12x/12 = - 37/12
Since 12/12 is equal to 1 our value of x would be
x = - 37/12
Or simply x = - 3.0833
Now that we know the value of x we can use it to obtain the value of y
y = - 2x - 9
y = - 2(-37/12) - 9
y = 37/6 - 9
y = - 17/6
Or in decimal y = - 2.8333
Final values of x and y would be
x = - 3.0833
y = - 2.8333
Answer:
The solution of this system of equations : (-3.08,-2.84)
Step-by-step explanation:
Given : [tex]6x-3y+10=0\\\\2x+y+9=0[/tex]
To Solve : system of liner equations
Solution :
We are given the equations :
6x-3y+10=0 -----(a)
2x+y+9=0 -----(b)
Now, solve these equatons using substitution method
Substitute the value of (y) from b in (a)
⇒6x-3(-9-2x)+10=0
⇒6x+27+6x)+10=0
⇒12x+27+10=0
⇒12x+37=0
⇒[tex]x = \frac{-37}{12}[/tex]
⇒[tex]x = -3.08[/tex]
Now to find value of y
put this value of x in equation (b)
⇒2(-3.08) + y + 9 = 0
⇒-6.16+ y + 9 = 0
⇒2.84+y=0
⇒y = -2.84
Thus the solution of this system of equations : (-3.08,-2.84)